Prevalence of insect pests on maize crop in District Mansehra, Khyber Pakhtunkhwa, Pakistan - Khan,Z. (2024)
Abstract The maize crop is used as food for humans, livestock and poultries forms, it is also used in bread making, corn flakes, corn syrup, corn starch and corn oils. The field study consisted of one experimental trial, about the incidence of that insect pest complex on maize cultivar Azam during the Kharif season 2020 at the Agricultural, Research Station, Baffa, Mansehra. The trial was laid out in the Randomized Complete Block Design (RCBD), and then it was divided into three replications. The result obtained from the trial showed that a number of the pest species were recorded during the experimental period; however, the population was noticed at a low level. The obtained insect species were corn leaf aphid (6.90 ± 5.5) per square inch, corn leafhopper (1.32 ± 0.63), maize stem borer (0.63 ± 0.29), corn flea beetle (0.43 ± 0.28), Thrips (0.38 ± 0.22), Hairy caterpillar (0.21 ± 0.22), Grasshopper (0.17 ± 0.11) and shoot fly (0.11 ± 0.08) throughout the season